Biomechanics of the spine : basic concepts, spinal disorders and treatments - Galbusera, Fabio; Wilke, Hans-Joachim (Professor for biomechanics) (Academic Press, 2018)
Biomechanics of the Spine encompasses the basics of spine biomechanics, spinal tissues, spinal disorders and treatment methods. Organized into four parts, the first chapters explore the functional anatomy of the spine, with special emphasis on aspects which are biomechanically relevant and quite often neglected in clinical literature. The second part describes the mechanics of the individual spinal tissues, along with commonly used testing set-ups and the constitutive models used to represent them in mathematical studies. The third part covers in detail the current methods which are used in spine research: experimental testing, numerical simulation and in vivo studies (imaging and motion analysis). The last part covers the biomechanical aspects of spinal pathologies and their surgical treatment. This valuable reference is ideal for bioengineers who are involved in spine biomechanics, and spinal surgeons who are looking to broaden their biomechanical knowledge base. The contributors to this book are from the leading institutions in the world that are researching spine biomechanics.